Artificial neural networks applied to power flow solution in electrical power system / Mohd Hashimi Hashim - Hashim, Mohd Hashimi (1995)
Artificial Neural Networks (ANNs) recently has gain momentum as tools for solving a complex system operating states which is dependent on several operating parameters. Basically the study is to identify the best Artificial Neural Networks model which gives the Artificial Neural Networks performance. Several Artificial Neural Networks models are tested and the best model is obtained which gives the best convergence